Teacher's Ability to Develop Learning Materials Potentially Mathematical Discourse - Hamdani Hamdani (STKIP Singkawang, 2017)
In the process of learning in the field, the teacher still dominates the conversation while the students as a passive listener. As a result, not only the communication skills of students who are less developed, the understanding of student material is also lacking. Therefore it is necessary to research the ability of teachers in developing learning tools potentially mathematical discourse to improve students' mathematical communication skills. The research method used is descriptive. Research activities include: identification of problems through questionnaires, observation, and interviews; teacher training; teachers develop learning tools; validation; and enhancement of the device by the teacher. The subject of this research is the junior high school mathematics teacher from several districts in the border area of Sambas-Sarawak Regency. The results show that in every learning mathematics there is always a conversation between teachers and students, but rarely use the question